2005
DOI: 10.1021/jp051163i
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and Diffusion of Singlet Oxygen in a Cell

Abstract: In time- and spatially resolved experiments, singlet molecular oxygen, O(2)(a(1)Delta(g)), was created in a single nerve cell upon irradiation of a sensitizer incorporated in the cell nucleus using a focused laser beam. The singlet oxygen thus produced was detected by its infrared phosphorescence. Data obtained indicate that, contrary to common perception, this reactive species can be quite long-lived in a cell and, as such, can diffuse over appreciable distances including across the cell membrane into the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
378
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(394 citation statements)
references
References 28 publications
13
378
2
1
Order By: Relevance
“…[13][14][15][16] Specifically, for D 2 O-incubated cells, we repeatedly find that the lifetimes determined both in the cytoplasm and in the nucleus (~ 30-40 µs) are shorter than that for singlet oxygen in pure D 2 O (67 µs). These data point to a non-negligible k c [C] term, [13][14][15][16] as is indeed expected given that singlet oxygen can induce cell death. The quenching plots obtained using the NaN 3 equals the extracellular concentration in the incubating medium, the data in Figure 5 suggest that this intracellular quenching occurs at the diffusion-controlled limit.…”
Section: When Incorporated Into Hela Cells Tmpyp Ultimately Tends Tomentioning
confidence: 62%
“…[13][14][15][16] Specifically, for D 2 O-incubated cells, we repeatedly find that the lifetimes determined both in the cytoplasm and in the nucleus (~ 30-40 µs) are shorter than that for singlet oxygen in pure D 2 O (67 µs). These data point to a non-negligible k c [C] term, [13][14][15][16] as is indeed expected given that singlet oxygen can induce cell death. The quenching plots obtained using the NaN 3 equals the extracellular concentration in the incubating medium, the data in Figure 5 suggest that this intracellular quenching occurs at the diffusion-controlled limit.…”
Section: When Incorporated Into Hela Cells Tmpyp Ultimately Tends Tomentioning
confidence: 62%
“…However, Zhuang et al reported that attenuation of EGFR after Rose Bengal(RB)-PDT was dependent on activation of both caspase-3 and protein phosphatases (Zhuang et al 2003). The decreased EGFR activation after endo/lysosomal PDT observed in paper III can also be (Skovsen et al 2005, Hatz et al 2007 and it is not unlikely that this ROS can diffuse across the 10-20 nm tick plasma membrane. On the other hand, singlet oxygen will be easily quenched by biomolecules in the plasma membrane (Bronshtein et al 2004) and more research is required to conclude on the mechanisms causing the damage of EGFR in TPPS 2a -treated cells.…”
Section: Tpps 2a -Pdt Induced Damage To Egfrmentioning
confidence: 91%
“…Most of the 1 O 2 generated in the membrane would diffuse from the membrane and react with components in the water space [29,36,37]. Recent results studying the decay of 1 O 2 in single cells suggest its lifetime to be more than an order of magnitude greater in the water space of cells than previously thought [34,35]. Thus singlet oxygen would have a diffusion distance greater than currently accepted, although much less than H 2 O 2 .…”
Section: Introductionmentioning
confidence: 93%
“…Hydrogen peroxide is a highly diffusible oxidant that could expand the damage inflicted by 1 O 2 . It has been shown that 1 O 2 will readily diffuse from the interior of, or across a hydrophobic volume, such as a membrane, into the neighboring aqueous space [26,27,28,29,30,31,32,33,34,35]. Most of the 1 O 2 generated in the membrane would diffuse from the membrane and react with components in the water space [29,36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation